Infrapatellar Saphenous Neuralgia After TKA Can Be Improved With Ultrasound-guided Local Treatments - Clendenen, Steven (Clin Orthop Relat Res, 2014)
BACKGROUND: Current opinion suggests that in some patients, chronic pain after total knee arthroplasty (TKA) has a neuropathic origin. Injury to the infrapatellar branch of the saphenous nerve (IPSN) has been implicated as a cause of medial knee pain; however, local treatments for this condition remain controversial. QUESTIONS/PURPOSES: We sought to explore the efficacy of local treatment to the IPSN in patients with persistent medial knee pain after TKA. METHODS: In this retrospective series, 16 consecutive patients with persistent medial knee pain after primary or revision TKA were identified after other potential etiologies of knee pain were excluded. Using advanced ultrasound imaging to identify the IPSN, hydrodissection of the nerve from the adjacent interfascial planes was performed followed by corticosteroid injection (local treatment). In two patients, radiofrequency ablation of the IPSN was subsequently performed for recurrent symptoms. The outcome measure of this study was patient-reported relief of medial knee pain based on a visual analog scale (VAS) score of 0 to 10 either at rest or with activity, whichever resulted in more pain for the patient. Followup was at a minimum of 6 months (median, 9 months; range, 6–12 months). Before the procedure, the median highest VAS pain score, either at rest or with activity, was 8 of 10 (range, 6–10). RESULTS: Local injections to the infrapatellar saphenous nerve (one or two injections) improved medial pain after TKA to a VAS score of 0 or 1 in nine of our 16 patients. Three patients reported pain improvement to VAS levels of 3 to 4. Of the remaining four patients, two did not have improvement with VAS scores of 8, and two underwent subsequent radiofrequency ablation of the IPSN with resolution of pain in one patient. CONCLUSIONS: In summary, we believe injury to the IPSN may be an underappreciated cause of persistent medial pain after TKA. We report favorable preliminary results with local treatment to the nerve in nine of our 16 patients, suggesting that the neuritis is a reversible process in some patients; however, because of the possibility of a placebo effect, we believe this treatment modality should be tested in a randomized, placebo-controlled trial. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.